2014
DOI: 10.1007/s13304-014-0267-y
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy in octogenarians: be careful

Abstract: Cholecystectomy is the standard treatment for symptomatic gallstone or acute cholecystitis, and a growing number of elderly patients are undergoing resection. The aim of this study is to evaluate the clinical outcome of cholecystectomy in elderly patients. We retrospectively reviewed the medical records of 337 patients with symptomatic gallstone or acute cholecystitis who underwent cholecystectomies between January 2011 and June 2013. Perioperative data were compared between octogenarians and younger patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 11 publications
3
39
2
3
Order By: Relevance
“…Yet, 4 of the 5 included studies comparing perioperative outcomes of early cholecystectomy in elderly and younger patients showed no significant difference in terms of perioperative morbidity or mortality [17][18][19]21] . Only one study proved older age to be independently associated with increased morbidity [20] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Yet, 4 of the 5 included studies comparing perioperative outcomes of early cholecystectomy in elderly and younger patients showed no significant difference in terms of perioperative morbidity or mortality [17][18][19]21] . Only one study proved older age to be independently associated with increased morbidity [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Minor complications such as wound infections were also frequently encountered but had minor impact on the final outcome. It is noteworthy that only 2 studies [17,19] reported on the severity of each complication, both by using the Clavien-Dindo classification [26] . The remaining studies neither mentioned the severity of the complications nor whether the patients had fully recovered from the complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations